Methylprednisolone in the management of post-COVID-19 interstitial lung disease: A randomized trial (STERCOV-ILD) - Yüksel, Aycan; Karadoğan, Dilek; Hürsoy, Nur; Telatar, Tahsin Gökhan; Köse Kabil, Neslihan; Marım, Feride; Kaya, İlknur and Er, Aslıhan Banu and Erçelik, Merve and Polat Yuluğ, Demet and Yumrukuz Şenel, Merve and İlgar, Ceren and Gültekin, Ökkeş and Çakmakcı Karakaya, Selin and Yılmaz Kara, Bilge and Özçelik, Neslihan and Selimoğlu, İnci and Uyar Er, Kübra and Kotan, Abdurrahman and Keskin, Hasan Veysel and Akgün, Metin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: Post-COVID-19 Interstitial Lung Disease (ILD) is controversial and need for treatment is unclear.The aim of this study was to investigate the efficacy of methylprednisolone in the management of post-COVID-19 ILD in comparison to standard of care. Methods: In this multicentre, randomized controlled clinical trial, patients with post-COVID ILD were assigned to two groups: the steroid group received oral methylprednisolone at a dose of 0.5 mg/kg/day, while the control group received supportive therapy. The primary outcome was proportion of patients with functional improvement (defined as the absence of hypoxemia/desaturation during 6MWT) at twelve-weeks. Results: A total of 229 patients with post-COVID ILD patients (124 in the steroid group and 104 in the control group) completed the study. At 12-weeks, functional improvement rate was higher in the steroid group compared to the control group (74.2% vs. 55.2%, OR:2.33 [95% CI:1.34–4.06], p=0.0041). Radiological improvement was observed in 61.3% of the steroid group compared to 46.7% of the controls (OR:1.81 [95% CI:1.07–3.06], p=0.037). The mean increase in FVC (7.2% vs 3.7%, p=0.03), 6MW distance (91 vs 41 meters, p<0.001), and SpO2 (2.33 vs 1.21, p=0.002) was significantly higher in the steroid group. Multivariate regression analysis revealed that the following variables were associated with poorer outcomes: smoking (OR:0.932 [95% CI:0.875–0.992], p=0.028), older age (OR:0.951 [95% CI:0.912-0.99], p=0.035), and severe COVID-19 (OR:0.233 [95% CI:0.068–0.799], p=0.029. Conclusions: Methylprednisolone improved oxygen saturation, FVC, exercise capacity, and radiological resolution in patients with post-COVID-19 ILD compared to the natural course of the disease.